The Quality of Aid for Trade Flows and Economic Complexity - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2023)
The few existing studies on the effect of Aid for Trade (AfT) flows on economic complexity have reached inconclusive outcomes. The present analysis re-examines this issue through the lens of the concept of 'quality of AfT flows' that takes into account not only the amount of AfT flows, but also the predictability and volatility of these capital inflows. A country enjoys a better quality of AfT flows if it receives higher AfT flows in a predictable and less volatiles fashions. We investigate the effect of the quality of AfT flows on economic complexity, over a set of 86 countries and the period from 2004 to 2019, and using the within fixed effects estimator and the Method of Moments Quantile Regression with fixed effects approach. The findings suggest that not only does a better quality of AfT flows fosters economic complexity in recipient countries, but its positive effect is larger in less complex economies (including poorest countries) than in relatively more complex economies among recipient countries. These findings reveal that what really matters for the enhancement of economic complexity in developing countries may not be only the amounts of the total AfT flows, but more importantly the predictability and the stability of these resource inflows. Improving the quality of AfT flows by increasing AfT amounts in a predictable and stable fashions would be beneficial to developing countries, and particularly to a greater extent to poorest countries among them.
Keywords: O11; O14; F14; F35; 330; Aid for Trade; Predictability of Aid for Trade; Volatility of Aid for Trade; Economic complexity